A safe and effective modification of Thomson's jumping ring experiment - Waschke, Felix; Strunz, Andreas; Meyn, Jan-Peter (European Journal of Physics, 2012)
UnivIS-Import:2015-03-09:Pub.2012.nat.dphy.PI.PDP.asafea

Demonstrating quantum random with single photons - Bronner, Patrick; Strunz, Andreas; Silberhorn, Christine; Meyn, Jan-Peter (European Journal of Physics, 2009)
We present an experiment for education which demonstrates random transmission or reflection of heralded single photons on beam splitters. With our set-up, we can realize different quantum random experiments by appropriate settings of polarization rotators. The concept of entanglement is motivated by correlated randomness. The experiments are suitable for undergraduate education and are available as interactive screen experiments. © 2009 IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.PI.PDP.demons

Experimentelle Quantenphysik im Physikunterricht - Strunz, Andreas; Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2015)
Wir demonstrieren die Quantennatur des Lichts mit einer neu entwickelten Apparatur im Klassenzimmer. Einzelphotonenzustände werden mit einer Koinzidenzmethode präpariert. Die Auswertung von Signalen zweier Detektoren hinter einem halbdurchlässigen Spiegel ergibt eine Antikorrelation, die als Reflexion oder Tranmission einer unteilbaren Lichtportion interpretiert wird. Dass es sich dabei nicht um mechanistisch gedachte Teilchen handeln kann, ergibt die anschließende Interferenz in einem Michelson-Interferometer. Experimentelle Methoden und Begriffe entsprechen dem aktuellen Stand der Physik.

Interactive screen experiments with single photons - Bronner, Patrick; Strunz, Andreas; Silberhorn, Christine; Meyn, Jan-Peter (European Journal of Physics, 2009)
Single photons are used for fundamental quantum physics experiments as well as for applications. Originally being a topic of advance courses, such experiments are increasingly a subject of undergraduate courses. We provide interactive screen experiments (ISE) for supporting the work in a real laboratory, and for students who do not have access to a quantum optics laboratory. The main focus of the ISE is on undergraduate education, but some of the experiments are suitable for other levels of higher education as well. © 2009 IOP Publishing Lt
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.PI.PDP.intera

Photonik macht Schule - Ein Schülerlabor zur modernen Optik und Quantenoptik - Vetter, Andreas; Strunz, Andreas; Bronner, Patrick; Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2010)
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.PI.PDP.photon

Quantitative analysis of a wind energy conversion model - Zucker, Florian; Strunz, Andreas; Gräbner, Anna; Meyn, Jan-Peter (European Journal of Physics, 2015)
A rotor of 12 cm diameter is attached to a precision electric motor, used as a generator, to make a model wind turbine. Output power of the generator is measured in a wind tunnel with up to 15 m s-1 air velocity. The maximum power is 3.4 W, the power conversion factor from kinetic to electric energy is cp = 0.15. The v3 power law is confirmed. The model illustrates several technically important features of industrial wind turbines quantitatively.
UnivIS-Import:2015-04-14:Pub.2015.nat.dphy.PI.PDP.quanti
Keywords: Betz factor; demonstration experiment; model; renewable energy; wind energy; wind turbine

"Und er würfelt doch!" - Optische Experimente zum Quantenzufall - Bronner, Patrick; Strunz, Andreas; Silberhorn, Christine; Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dphy.PI.PDP.underw